1995
DOI: 10.1074/jbc.270.51.30611
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tricyclic Inhibitors of Farnesyl Protein Transferase

Abstract: Oncogenic forms of Ras proteins are associated with a broad range of human cancers including an estimated 90% of all colon cancers (1). Ras proteins undergo a complex series of posttranslational processing events, which have been defined over the past several years (2, 3). The initial post-translational event is the transfer of the 15-carbon isoprene farnesyl from farnesyl pyrophosphate to a Cys residue (Cys 186 in Ha-Ras) in the conserved carboxyl-terminal "CAAX" motif (where "A" is an aliphatic residue) pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 41 publications
0
93
0
Order By: Relevance
“…FTI-277 and GGTI-298 are the methyl ester prodrugs of the free acids FTI-276 and GGTI-297, respectively. FTI-277, L-745,631, SCH-44342, and GGTI-298 apparently penetrate into cells because they block Ras farnesylation or Rap 1A geranylgeranylation in mammalian cells (31,67,68). As reported previously, the Merck compound L-745,631 inhibits mammalian PFT in the low nanomolar range and is highly selective for PFT over PGGT-I (Table II).…”
Section: Inhibition Of T Brucei Pft By Caaxmentioning
confidence: 70%
“…FTI-277 and GGTI-298 are the methyl ester prodrugs of the free acids FTI-276 and GGTI-297, respectively. FTI-277, L-745,631, SCH-44342, and GGTI-298 apparently penetrate into cells because they block Ras farnesylation or Rap 1A geranylgeranylation in mammalian cells (31,67,68). As reported previously, the Merck compound L-745,631 inhibits mammalian PFT in the low nanomolar range and is highly selective for PFT over PGGT-I (Table II).…”
Section: Inhibition Of T Brucei Pft By Caaxmentioning
confidence: 70%
“…The observed e ects include morphological changes, inhibition of anchorage-independent growth and alteration of cell cycle progression (Garcia et al, 1993;James et al, 1993;Kohl et al, 1993;Prendergast et al, 1994;Bishop et al, 1995;Sepp-Lorenzino et al, 1995;Vogt et al, 1997;Suzuki et al, 1998a). We, as well as others, have recently shown that FTI is capable of inducing apoptosis of cancer cell lines (Lebowitz et al, 1997;Hung and Chuang, 1998;Suzuki et al, 1998b;Du et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…The primary driving force for such efforts came from the finding that oncogenic forms of Ras proteins require farnesylation for their ability to transform cells. Inhibitors of FTase that have been synthesized or identified include analogs of both substrates (41)(42)(43)(44), fused forms of the two substrates (45), and a number of natural products and other compounds identified in screening programs (46,47). Many of these inhibitors block Ras processing and inhibit the growth of Ras-transformed cells (41).…”
Section: Farnesyltransferase Inhibitor Studiesmentioning
confidence: 99%